ANALISIS BAURAN PEMASARAN JAMUR TIRAM DI KOTA PEKANBARU - Sabam Mael Beri M; Eliza '; Fajar Restuhadi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The research aims to figure out the characteristic of Oyster Mushroom in Pekanbaru, the level of belief, consumers’ importance and consumers’ attitude on marketing mix of Oyster Mushroom in Pekanbaru. The research was carried out on Limbungan street BPD Complex in Rumbai Pekanbaru. This research used primary data that was gained from interview and secondary data that was gained from Board of Statistic Center and other references, and then those data were analayzed by using validity and reliability test, importance and belief level, cartesian diagram, Multiattribute Fishbein. The result showed that the biggest number of consumers’ chracteristicswere in productive age41-50 years old, female, mostly in S1 and High School as the educational level, and jobs were housewife and private employee, with 2-3 children, with income range between Rp. 3,000,000-Rp.5,000,000/month, and have been subscribing for 4-6 months. The attributes of Oyster Mushroom producer with above the average level of belief were the affordable price, discount, reachable location, packaging, texture, benefit, nutrients, and expiry. The attributes with below the average level of belief were the price that was cheaper than other types of mushroom, parking area, the street condition, hygiene and the place comfortability, promotion in newspaper and billboard. The attributes of Oyster Mushroom producer with above the average level of importance were affordable price, discount, reachable location, good street condition, hygiene, and the place comfortability, product availibility, texture, benefit, nutrients, and expiry. The consumers’ attitude toward the Oyster Mushroom producer according to the scale score was 436.2273it was located in “a bit agree scale of measurement” (5), therefore the consumers’ attitude in the research was chategorized as “a bit agree” in scale of measurement.   Keywords:Oyster Mushroom, marketing mix, consumers,attributes, attitude.